Constrains in Educational Development in Indonesia: A Case in Southeast Sulawesi Province - Lio, Asrun (International Journal of Management and Education in Human Development, 2021)
During my works experiences, I took part in a number of important activities in educational development where I acted as consultant in the educational development project in Southeast Sulawesi I can note down some issues such as the transparency among and across the stakeholders has not developed, luck of professional commitment of stakeholders (individually and in group) to change the situation, over-reliance on project-oriented planning rather than on the nurturing of natural chance processes, over-reliance on the results of the national state exams as the total performance indicators, over-emphasis on the product rather than process, and lack of concern for the welfare of all the parties concerned. In this paper, I would like to gather evidence some crucial issues with respect empirical informations on education development in Southeast Sulawesi. The issues include local government commitment or policy related to educational development in the region, the performance evaluation of certified teachers, and the role of university or teacher training institution as teacher service provider related to teacher training and professionalism (Indo: PLPG - Pendidikan Latihan Profesi Guru). Identifying and understanding educational constrains in this area could assist both central and local government in designing and implementing educational programs to improve the quality of education.